JWST NIRCam Observations of SN 1987A: Spitzer Comparison and Spectral Decomposition - Arendt Richard G.; Boyer Martha L.; Dwek Eli; Matsuura Mikako; Ravi Aravind P.; Rest Armin; Chevalier Roger; Cigan Phil; De Looze Ilse; De Marchi Guido; Fransson Claes; Gall Christa; et al. (Institute of Physics Publishing, 2025)
JWST Near Infrared Camera (NIRCam) observations at 1.5–4.5 μm have provided broadband and narrowband imaging of the evolving remnant of SN 1987A with unparalleled sensitivity and spatial resolution. Comparing with previous marginally spatially resolved Spitzer Infrared Array Camera (IRAC) observations from 2004 to 2019 confirms that the emission arises from the circumstellar equatorial ring (ER), and the current brightness at 3.6 and 4.5 μm was accurately predicted by extrapolation of the declining brightness tracked by IRAC. Despite the regular light curve, the NIRCam observations clearly reveal that much of this emission is from a newly developing outer portion of the ER. Spots in the outer ER tend to lie at position angles in between the well-known ER hotspots. We show that the bulk of the emission in the field can be represented by five standard spectral energy distributions, each with a distinct origin and spatial distribution. This spectral decomposition provides a powerful technique for distinguishing overlapping emission from the circumstellar medium and the supernova ejecta, excited by the forward and reverse shocks, respectively.